A kind of poly 2,5-furandicarboxylic acid alcohol ester based thermoplastic polyester elastomer and preparation method thereof

Through the prefabricated section of the prefabricated section of the prefabricated chain in the polymerinol ester, the thermoplastics polyester elastic body is prepared, and the problem of insufficient molecular structure in the existing technology and the lack of biodegradation performance in the existing technology have been solved. Multiple aspects of performance regulation and wide application.

CN115850671BActive Publication Date: 2025-01-28QINGDAO UNIV OF SCI & TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211465219.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-22
Publication Date
2025-01-28
Estimated Expiration
2042-11-22

AI Technical Summary

Technical Problem

The existing thermoplastic polyester elastomers have shortcomings in both designing molecular structure, adjustable molecular weight, good biodegradability, simple preparation method, and low requirements for production equipment, which limits their application in related fields.

Method used

Adopt a polygage 2,5-amuxyl glycogenate as the main monomer, and the A-B-B polymer 2,5-amuxyramate-polymer-clustering is prepared by the prefabricated Entry sections of common clusters to regulate their molecular structure and soft and hard segment ratio.

Benefits of technology

The effective regulation of the molecular structure and performance of the polyte 2,5-amuxyl glycolitate-based thermoplastic polyester elastic body has good mechanical performance, thermal performance and biodegradation performance, and is suitable for a variety of application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003957197800000241
    Figure BDA0003957197800000241
Patent Text Reader

Abstract

The present invention provides a poly-2,5-furandicarboxylic acid alcohol ester-based thermoplastic polyester elastomer and a preparation method thereof, and belongs to the technical field of polymer materials. The poly-2,5-furandicarboxylic acid alcohol ester-based thermoplastic polyester elastomer prepared by the present invention can effectively regulate the molecular structure, molecular weight and soft segment to hard segment ratio, thereby controlling its mechanical properties, thermal properties and degradation properties, so that it meets the use requirements and improves its application range. The preparation method is simple, no organic waste liquid is generated, and it is suitable for large-scale production. And the poly-2,5-furandicarboxylic acid alcohol ester-based thermoplastic polyester elastomer prepared by the present invention is a biodegradable green polymer material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and particularly relates to a poly-2,5-furandicarboxylate-based thermoplastic polyester elastomer and a preparation method thereof. Background Art

[0002] Aromatic polyesters containing six-membered benzene ring structures, such as polyethylene terephthalate (PET) and polybutylene terephthalate (PBTE), are commonly used in the preparation of hard segment polyesters in thermoplastic polyester elastomers (TPEs), imparting excellent mechanical strength to these TPEs. However, the high crystallinity and benzene ring structure of PET and PBT make TPEs less biodegradable, potentially causing environmental pollution. 2,5-Furandicarboxylic acid (2,5-Furandicarboxylic acid) is an aromatic monomer derived from renewable biomass resources. Its molecular structure contains a furan ring containing a five-membered oxygen heterocycle, which is capable of ring-opening, making 2,5-Furandicarboxylic acid-based polyesters highly biodegradable. For example, patent CN107312167A discloses a thermoplastic polyester elastomer based on biomass-based 2,5-furandicarboxylic acid and its preparation method. The specific method involves mixing 2,5-furandicarboxylic acid, an aliphatic diol, an aliphatic lactone, and related additives, followed by esterification, ring-opening, and polycondensation to produce the corresponding thermoplastic polyester elastomer. The molecular structure of the thermoplastic elastomer produced by this method is difficult to control. Patent CN111116880A discloses a fully bio-based thermoplastic polyester elastomer based on a furan ring and its preparation method. The specific method involves first preparing a hydroxyl-terminated bio-based polyester soft segment, then mixing it with 2,5-furandicarboxylic acid or its ester and a bio-based diol. Esterification or transesterification and polycondensation reactions are then performed to produce the corresponding thermoplastic polyester elastomer. The structure and properties of the thermoplastic polyester elastomer produced by this method are difficult to control.

[0003] The existing preparation technology of thermoplastic polyester elastomers cannot combine the advantages of designable molecular structure, adjustable molecular weight and soft and hard segment ratio, good biodegradability, simple preparation method, and low requirements for production equipment, which greatly limits its application in related fields. Summary of the Invention

[0004] In response to the above-mentioned shortcomings, the present invention provides a thermoplastic polyester elastomer based on poly 2,5-furandicarboxylate, which has a designable molecular structure, controllable molecular weight, good biodegradability, a simple preparation method, and low requirements for production equipment, and a preparation method thereof.

[0005] In order to achieve the above-mentioned object of the invention, the technical solution of the present invention is as follows:

[0006] On the one hand, the present invention provides a poly 2,5-furandicarboxylic acid alcohol ester-based thermoplastic polyester elastomer, wherein the thermoplastic polyester elastomer is an AbB-type poly 2,5-furandicarboxylic acid alcohol ester-polyester block copolymer synthesized by block-polymerizing prepolymer A and prepolymer B with a chain extender; the prepolymer A is a 2,5-furandicarboxylic acid polyester prepolymer with a dihydroxy or carboxyl group end-capping prepared by polymerizing a diol with 2,5-furandicarboxylic acid or 2,5-furandicarboxylic acid dimethyl ester; and the prepolymer B is a highly flexible aliphatic polyester prepolymer with a dihydroxy or carboxyl group end-capping prepared by melt polycondensation using a variety of aliphatic diols and dibasic acids (or acid anhydrides, acid chlorides) as monomers.

[0007] Furthermore, the mass ratio of the prepolymer A to the prepolymer B is 1:1-1:19.

[0008] Furthermore, the ratio of the molar number of functional groups in the chain extender to the molar number of hydroxyl or carboxyl groups in the prepolymer is 1:1-1.3:1. Preferably, the ratio of the molar number of functional groups in the chain extender to the molar number of hydroxyl or carboxyl groups in the prepolymer is 1.25:1.

[0009] Furthermore, the number average molecular weight of the prepolymer A is 1,000-20,000.

[0010] Furthermore, the diol is one of ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 2-methyl-1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,10-decanediol, diethylene glycol, dipropylene glycol, triethylene glycol, tripropylene glycol, PEG-200, PEG-400, PEG-600, PPG-200, PPG-400, PPG-600, or a mixture thereof in any proportion.

[0011] Furthermore, the number average molecular weight of the highly flexible aliphatic polyester prepolymer B is in the range of 1000-20000; the glass transition temperature of the aliphatic polyester prepolymer B is lower than -40°C; and the molecular structure of the aliphatic polyester prepolymer B is composed of four or more aliphatic polyester repeating structural units.

[0012] Furthermore, the dibasic acid (or acid anhydride, acid chloride) is any one of oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, sebacic acid, dodecanedioic acid, tridecanedioic acid, pentadecandioic acid, itaconic acid, fumaric acid, succinic anhydride, glutaric anhydride, adipic anhydride, itaconic anhydride, maleic anhydride, succinic acid dichloride, glutaric acid dichloride, adipic acid dichloride, itaconic acid chloride, or a mixture thereof in any proportion.

[0013] Furthermore, the chain extender is hexamethylene diisocyanate (HDI), diphenylmethane diisocyanate (MDI), dicyclohexylmethane diisocyanate (HMDI), isophorone diisocyanate (IPDI), lysine diisocyanate (LDI), 2,4-toluene diisocyanate (TDI), 2,6-toluene diisocyanate, naphthalene diisocyanate (NDI), bis((3,4-epoxycyclohexyl)methyl) adipate, 1,6-hexanedioic acid diglycidyl ether, resorcinol diglycidyl ether, 1,3-benzenediol diglycidyl ether, Hydroquinone formaldehyde tetraglycidyl ether, p-aminophenol epoxy resin, tetrahydrophthalate epoxy resin, 1,2-epoxycyclohexane 4,5-dicarboxylic acid epoxy resin, o-phthalate epoxy resin, isophthalate epoxy resin, p-terephthalate epoxy resin, endomethylene tetrahydrophthalate epoxy resin, p-hydroxybenzoic acid epoxy resin, bis(2,3-epoxycyclopentyl) ether, ethylene glycol diglycidyl ether, 2,2-bis(2-oxazoline) (BOZ), 2,2-(1,3-phenylene)-bisoxazoline (PBO) or a mixture thereof in any proportion.

[0014] On the other hand, the present invention provides a method for preparing the poly-2,5-furandicarboxylate-based thermoplastic polyester elastomer as described above, comprising the following steps:

[0015] (1) Preparation of prepolymer A

[0016] A diol and 2,5-furandicarboxylic acid or dimethyl 2,5-furandicarboxylate are mixed in a molar ratio of 0.8-3:1, a catalyst accounting for 0.01-0.5% of the weight of the monomers and a certain amount of antioxidant and stabilizer are added, and an esterification or transesterification reaction is carried out at a temperature range of 150-200° C. under nitrogen protection for 1-10 hours. Then, a certain amount of antioxidant and catalyst are added, and the temperature is raised to 200-270° C. within a pressure range below 2 kPa, and the reaction is continued for 1-8 hours to prepare a dihydroxy or carboxyl terminated hard segment prepolymer A;

[0017] (2) Preparation of prepolymer B

[0018] A plurality of aliphatic diols and dibasic acids are mixed at an alcohol-acid ratio of 1:1.05-1.5 or 1.05-1.5:1, a catalyst accounting for 0.01-0.5% of the monomer mass and a certain amount of antioxidant and stabilizer are added, and the mixture is stirred under an inert atmosphere and heated in stages to 130-180°C for esterification reaction for 1-6 hours. Thereafter, an antioxidant is added, and the mixture is stirred and heated to 200-240°C under a pressure range below 2 kPa, and the reaction is continued for 2-8 hours to obtain a highly flexible aliphatic polyester soft segment prepolymer B terminated with dihydroxy or carboxyl groups;

[0019] (3) Preparation of poly(2,5-furandicarboxylate)-based thermoplastic polyester elastomer

[0020] The prepolymer A and prepolymer B obtained in the above steps are mixed, heated to 140-250° C., melt-mixed for 20-60 minutes under nitrogen protection, and then a chain extender is added for block copolymerization. The reaction is carried out for 10-60 minutes, and then the reaction is continued for 0.5-2 hours under a pressure range of a vacuum degree of less than 2 kPa, thereby preparing a poly-2,5-furandicarboxylate-based thermoplastic polyester elastomer.

[0021] Furthermore, the stirring and dispersing method is mechanical stirring, magnetic stirring or ultrasonic vibration.

[0022] Furthermore, the catalyst is selected from sulfuric acid, trifluoromethanesulfonic acid, methyl trifluoromethanesulfonate, titanium dioxide, titanium glycol, titanium acetylacetonate, n-butyl titanate, isopropyl titanate, antimony glycol, antimony trioxide, antimony acetate, stannous octoate, stannous oxalate, dibutyltin oxide, dibutyltin dilaurate, butylstannoic acid, lithium acetate, potassium acetate, calcium acetate, magnesium acetate, barium acetate, zinc acetate, cobalt acetate, antimony acetate, lead acetate, manganese acetate, triisopropoxyaluminum, zinc acetate, zinc oxide, stannous chloride, concentrated sulfuric acid, p-toluenesulfonic acid, magnesium acetate, zinc acetate, zinc chloride, lithium chloride, germanium chloride, tin tetrachloride, potassium carbonate, triethylenediamine, triethylamine, zinc lactate or a mixture thereof in any proportion.

[0023] Furthermore, the antioxidant is selected from one of antioxidant 168, antioxidant 240, antioxidant 245, antioxidant 264, antioxidant 300, antioxidant 330, antioxidant 445, antioxidant 1010, antioxidant 1024, antioxidant 1035, antioxidant 1520, antioxidant 1076, antioxidant 1098, antioxidant 1330, antioxidant 1790, antioxidant 2246, and antioxidant 3114, or a mixture thereof in any proportion.

[0024] Furthermore, the stabilizer is selected from one or more mixtures of phosphoric acid, phosphorous acid, hypophosphorous acid, pyrophosphoric acid, ammonium phosphate, dimethyl phosphate, trimethyl phosphate, diphenyl phosphate, triphenyl phosphate, diphenyl phosphite, triphenyl phosphite, triethyl phosphate, ammonium phosphite, diammonium dihydrogen phosphate, p-hydroxyanisole, hydroquinone, o-methylhydroquinone, p-benzoquinone or benzoquinone triphenyl phosphite.

[0025] Compared with the prior art, the present invention has the following positive and beneficial effects:

[0026] (1) The poly-2,5-furandicarboxylate-based thermoplastic polyester elastomer prepared by the present invention can effectively regulate the molecular structure, molecular weight and ratio of soft segment to hard segment, thereby controlling its mechanical properties, thermal properties and degradation properties, so as to meet the use requirements and improve its application range.

[0027] (2) The present invention adopts a chain extension method to synthesize poly-2,5-furandicarboxylic acid alcohol ester-based thermoplastic polyester elastomer, and the chain extension reaction temperature is low, energy is saved, and industrial production is easy.

[0028] (3) The poly-2,5-furandicarboxylate-based thermoplastic polyester elastomer prepared by the present invention is a biodegradable green polymer material.

[0029] (4) The synthesis method of poly 2,5-furandicarboxylic acid alcohol ester-based thermoplastic polyester elastomer adopts a green and environmentally friendly esterification condensation reaction, which does not contain organic solvents and does not produce waste water, waste gas, waste residue and other three wastes, and is safe and environmentally friendly. DETAILED DESCRIPTION

[0030] The present invention will be further described in detail below with reference to specific examples. The following examples are not intended to limit the present invention but are merely intended to illustrate the present invention. The experimental methods used in the following examples are generally based on conventional conditions unless otherwise specified. The materials and reagents used in the following examples are all commercially available unless otherwise specified.

[0031] When numerical ranges are given in the examples, it should be understood that, unless otherwise specified herein, both endpoints of each numerical range and any value between the two endpoints may be selected. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the art to which the present invention belongs.

[0032] It is worth noting that the raw materials used in the present invention are all common commercially available products, and therefore their sources are not specifically limited.

[0033] Example 1

[0034] 1. 73.66 g (0.4000 mol) of dimethyl 2,5-furandicarboxylate, 39.72 g (0.6400 mol) of ethylene glycol, 0.1134 g (0.10% wt) of zinc acetate, 0.0567 g (0.05% wt) of trimethyl phosphate and 0.1701 g (0.15% wt) of antioxidant 1010 were added to a reactor filled with nitrogen and containing a mechanical stirring device and a thermometer, and the reaction was carried out at a temperature of 180° C. for 1 h, and then at a temperature of 190° C. for 3 h, during which nitrogen was continuously introduced into the reactor. After that, 0.1134 g (0.10% wt) of antimony trioxide was added, and the reaction temperature was gradually increased to 240° C., and the pressure inside the reactor was gradually reduced from one atmosphere to 1 kPa. Under these conditions, the reaction was carried out for 4 h to finally obtain a hydroxyl-terminated prepolymer A. The number average molecular weight was determined by gel permeation chromatography to be 4.5×10 3 .

[0035] 2. 49.60 g (0.4200 mol) of succinic acid, 61.38 g (0.4200 mol) of adipic acid, 84.95 g (0.4200 mol) of sebacic acid, 52.74 g (0.6930 mol) of 1,3-propylene glycol, 62.45 g (0.6930 mol) of 1,4-butanediol, 0.1556 g (0.05% wt) of antioxidant 168 and 0.1556 g (0.05% wt) of antioxidant 1010 were added to a mixture filled with nitrogen and containing a mechanical stirrer. In a reactor equipped with a stirring device and a thermometer, the reaction temperature was gradually increased from 140°C to 190°C, and the reaction was continued for 3 hours under stirring and nitrogen atmosphere. Then, 0.3111g (0.10% wt) of stannous oxalate, 0.4667g (0.15% wt) of antioxidant 168, and 0.4667g (0.15% wt) of antioxidant 1010 were added. The reaction temperature was gradually increased to 220°C, and the pressure in the reactor was gradually reduced from one atmospheric pressure to 1 kPa. The reaction was continued for 4 hours under stirring to finally obtain a hydroxyl-terminated prepolymer B. The number average molecular weight of the prepolymer was 9.7×10 3 The glass transition temperature of the composite was measured by differential scanning calorimetry to be -56.8°C.

[0036] 3. 3.00 g of prepolymer A and 17.00 g of prepolymer B were added to a reactor filled with nitrogen and equipped with a mechanical stirrer. The mixture was melt-mixed by mechanical stirring at 230°C. After the two prepolymers were completely melted, a chain extender, hexamethylene diisocyanate (HDI), was added. The ratio of the molar number of isocyanate groups in the chain extender to the molar number of hydroxyl groups in the two prepolymers was 1.25:1. After 30 minutes of reaction, the pressure in the reactor was gradually reduced from 1 atmosphere to 1 kPa. The reaction was continued for 30 minutes to obtain a poly-2,5-furandicarboxylate-based thermoplastic polyester elastomer. The number average molecular weight was measured by gel permeation chromatography to be 8.5×10 4 .

[0037] Comparative Example 1

[0038] 1. 49.60 g (0.4200 mol) of succinic acid, 61.38 g (0.4200 mol) of adipic acid, 84.95 g (0.4200 mol) of sebacic acid, 52.74 g (0.6930 mol) of 1,3-propylene glycol, 62.45 g (0.6930 mol) of 1,4-butanediol, 0.1556 g (0.05% wt) of antioxidant 168 and 0.1556 g (0.05% wt) of antioxidant 1010 were added to a nitrogen-filled, mechanically In a reactor equipped with a stirring device and a thermometer, the reaction temperature was gradually increased from 140°C to 190°C, and the reaction was continued for 3 hours under stirring and a nitrogen atmosphere. Subsequently, 0.3111 g (0.10% wt) of stannous oxalate, 0.4667 g (0.15% wt) of antioxidant 168, and 0.4667 g (0.15% wt) of antioxidant 1010 were added. The reaction temperature was gradually increased to 220°C, and the pressure in the reactor was gradually reduced from one atmospheric pressure to 1 kPa. The reaction was continued for 4 hours under stirring to finally obtain a hydroxyl-terminated polyester. The number average molecular weight of the polyester was 9.7×10 3 .

[0039] 2. 18.42 g (0.1000 mol) of dimethyl 2,5-furandicarboxylate, 8.07 g (0.1300 mol) of ethylene glycol, 121.38 g of hydroxyl-terminated polyester, and 0.2957 g (0.20% wt) of p-hydroxyanisole were added to a reactor filled with nitrogen and equipped with a mechanical stirrer and a thermometer. After stirring and melting, the mixture was subjected to transesterification reactions at 160°C for 1 hour, 170°C for 1 hour, and 180°C for 2 hours. 0.0739 g (0.05% wt) of tetrabutyl titanate was then added, the temperature was raised to 220°C, and the mixture was subjected to vacuum polycondensation for 4 hours to obtain a poly-2,5-furandicarboxylate-based thermoplastic polyester elastomer. The number average molecular weight of the elastomer was 7.1×10 4 .

[0040] Example 2

[0041] 1. 73.66 g (0.4000 mol) of dimethyl 2,5-furandicarboxylate, 39.72 g (0.6400 mol) of ethylene glycol, 0.1134 g (0.10% wt) of zinc acetate, 0.0567 g (0.05% wt) of trimethyl phosphate and 0.1701 g (0.15% wt) of antioxidant 1010 were added to a reactor filled with nitrogen and containing a mechanical stirring device and a thermometer, and the reaction was carried out at a temperature of 180° C. for 1 h, and then at a temperature of 190° C. for 3 h, during which nitrogen was continuously introduced into the reactor. After that, 0.1134 g (0.10% wt) of antimony trioxide was added, and the reaction temperature was gradually increased to 240° C., and the pressure inside the reactor was gradually reduced from one atmosphere to 1 kPa. Under these conditions, the reaction was carried out for 4 h to finally obtain a hydroxyl-terminated prepolymer A. The number average molecular weight was determined by gel permeation chromatography to be 4.5×10 3 .

[0042] 2. 49.60 g (0.4200 mol) of succinic acid, 61.38 g (0.4200 mol) of adipic acid, 84.95 g (0.4200 mol) of sebacic acid, 52.74 g (0.6930 mol) of 1,3-propylene glycol, 62.45 g (0.6930 mol) of 1,4-butanediol, 0.1556 g (0.05% wt) of antioxidant 168 and 0.1556 g (0.05% wt) of antioxidant 1010 were added to a mixture filled with nitrogen and containing a mechanical stirrer. In a reactor equipped with a stirring device and a thermometer, the reaction temperature was gradually increased from 140°C to 190°C, and the reaction was continued for 3 hours under stirring and nitrogen atmosphere. Then, 0.3111g (0.10% wt) of stannous oxalate, 0.4667g (0.15% wt) of antioxidant 168, and 0.4667g (0.15% wt) of antioxidant 1010 were added. The reaction temperature was gradually increased to 220°C, and the pressure in the reactor was gradually reduced from one atmospheric pressure to 1 kPa. The reaction was continued for 4 hours under stirring to finally obtain a hydroxyl-terminated prepolymer B. The number average molecular weight of the prepolymer was 9.7×10 3 The glass transition temperature of the composite was measured by differential scanning calorimetry to be -56.8°C.

[0043] 3. 2.00 g of prepolymer A and 18.00 g of prepolymer B were added to a reactor filled with nitrogen and equipped with a mechanical stirrer. The mixture was melt-mixed at 230°C by mechanical stirring. After the two prepolymers were completely melted, a chain extender, HDI, was added. The ratio of the molar number of isocyanate groups in the chain extender to the molar number of hydroxyl groups in the two prepolymers was 1.25:1. After 30 minutes of reaction, the pressure in the reactor was gradually reduced from 1 atmosphere to 1 kPa. The reaction was continued for 30 minutes to obtain a poly-2,5-furandicarboxylate-based thermoplastic polyester elastomer. The number average molecular weight was measured by gel permeation chromatography to be 8.8×10 4 .

[0044] Comparative Example 2

[0045] 1. 49.60 g (0.4200 mol) of succinic acid, 61.38 g (0.4200 mol) of adipic acid, 84.95 g (0.4200 mol) of sebacic acid, 52.74 g (0.6930 mol) of 1,3-propylene glycol, 62.45 g (0.6930 mol) of 1,4-butanediol, 0.1556 g (0.05% wt) of antioxidant 168 and 0.1556 g (0.05% wt) of antioxidant 1010 were added to a nitrogen-filled, mechanically In a reactor equipped with a stirring device and a thermometer, the reaction temperature was gradually increased from 140°C to 190°C, and the reaction was continued for 3 hours under stirring and a nitrogen atmosphere. Subsequently, 0.3111 g (0.10% wt) of stannous oxalate, 0.4667 g (0.15% wt) of antioxidant 168, and 0.4667 g (0.15% wt) of antioxidant 1010 were added. The reaction temperature was gradually increased to 220°C, and the pressure in the reactor was gradually reduced from one atmospheric pressure to 1 kPa. The reaction was continued for 4 hours under stirring to finally obtain a hydroxyl-terminated polyester. The number average molecular weight of the polyester was 9.7×10 3 .

[0046] 2. 18.42 g (0.1000 mol) of dimethyl 2,5-furandicarboxylate, 8.07 g (0.1300 mol) of ethylene glycol, 192.78 g of hydroxyl-terminated polyester, and 0.4385 g (0.20% wt) of p-hydroxyanisole were added to a reactor filled with nitrogen and equipped with a mechanical stirrer and a thermometer. After stirring and melting, the mixture was subjected to transesterification reactions at 160°C for 1 hour, 170°C for 1 hour, and 180°C for 2 hours. Then, 0.1096 g (0.05% wt) of tetrabutyl titanate was added, the temperature was raised to 220°C, and the mixture was subjected to vacuum polycondensation for 4 hours to obtain a poly-2,5-furandicarboxylate-based thermoplastic polyester elastomer. The number average molecular weight of the elastomer was 7.2×10 4 .

[0047] Example 3

[0048] 1. 73.66 g (0.4000 mol) of dimethyl 2,5-furandicarboxylate, 39.72 g (0.6400 mol) of ethylene glycol, 0.1134 g (0.10% wt) of zinc acetate, 0.0567 g (0.05% wt) of trimethyl phosphate and 0.1701 g (0.15% wt) of antioxidant 1010 were added to a reactor filled with nitrogen and containing a mechanical stirring device and a thermometer, and the reaction was carried out at a temperature of 180° C. for 1 h, and then at a temperature of 190° C. for 3 h, during which nitrogen was continuously introduced into the reactor. After that, 0.1134 g (0.10% wt) of antimony trioxide was added, and the reaction temperature was gradually increased to 240° C., and the pressure inside the reactor was gradually reduced from one atmosphere to 1 kPa. Under these conditions, the reaction was carried out for 4 h to finally obtain a hydroxyl-terminated prepolymer A. The number average molecular weight was determined by gel permeation chromatography to be 4.5×10 3 .

[0049] 2. 49.60 g (0.4200 mol) of succinic acid, 61.38 g (0.4200 mol) of adipic acid, 84.95 g (0.4200 mol) of sebacic acid, 52.74 g (0.6930 mol) of 1,3-propylene glycol, 62.45 g (0.6930 mol) of 1,4-butanediol, 0.1556 g (0.05% wt) of antioxidant 168 and 0.1556 g (0.05% wt) of antioxidant 1010 were added to a mixture filled with nitrogen and containing a mechanical stirrer. In a reactor equipped with a stirring device and a thermometer, the reaction temperature was gradually increased from 140°C to 190°C, and the reaction was continued for 3 hours under stirring and nitrogen atmosphere. Then, 0.3111g (0.10% wt) of stannous oxalate, 0.4667g (0.15% wt) of antioxidant 168, and 0.4667g (0.15% wt) of antioxidant 1010 were added. The reaction temperature was gradually increased to 220°C, and the pressure in the reactor was gradually reduced from one atmospheric pressure to 1 kPa. The reaction was continued for 4 hours under stirring to finally obtain a hydroxyl-terminated prepolymer B. The number average molecular weight of the prepolymer was 9.7×10 3 The glass transition temperature of the composite was measured by differential scanning calorimetry to be -56.8°C.

[0050] 3. 4.00 g of prepolymer A and 16.00 g of prepolymer B were added to a nitrogen-filled reactor equipped with a mechanical stirrer and melt-mixed at 230°C by mechanical stirring. After the two prepolymers were completely melted, a chain extender, HDI, was added, wherein the ratio of the number of moles of isocyanate in the chain extender to the number of moles of hydroxyl in the two prepolymers was 1.25:1. After 30 minutes of reaction, the pressure in the reactor was gradually reduced from 1 atmosphere to 1 kPa, and the reaction was continued for 30 minutes to obtain a poly-2,5-furandicarboxylate-based thermoplastic polyester elastomer. The number average molecular weight was measured by gel permeation chromatography to be 8.4×10 4 .

[0051] Comparative Example 3

[0052] 1. 49.60 g (0.4200 mol) of succinic acid, 61.38 g (0.4200 mol) of adipic acid, 84.95 g (0.4200 mol) of sebacic acid, 52.74 g (0.6930 mol) of 1,3-propylene glycol, 62.45 g (0.6930 mol) of 1,4-butanediol, 0.1556 g (0.05% wt) of antioxidant 168 and 0.1556 g (0.05% wt) of antioxidant 1010 were added to a nitrogen-filled, mechanically In a reactor equipped with a stirring device and a thermometer, the reaction temperature was gradually increased from 140°C to 190°C, and the reaction was continued for 3 hours under stirring and a nitrogen atmosphere. Subsequently, 0.3111 g (0.10% wt) of stannous oxalate, 0.4667 g (0.15% wt) of antioxidant 168, and 0.4667 g (0.15% wt) of antioxidant 1010 were added. The reaction temperature was gradually increased to 220°C, and the pressure in the reactor was gradually reduced from one atmospheric pressure to 1 kPa. The reaction was continued for 4 hours under stirring to finally obtain a hydroxyl-terminated polyester. The number average molecular weight of the polyester was 9.7×10 3 .

[0053] 2. 18.42 g (0.1000 mol) of dimethyl 2,5-furandicarboxylate, 8.07 g (0.1300 mol) of ethylene glycol, 85.68 g of hydroxyl-terminated polyester, and 0.2243 g (0.20% wt) of p-hydroxyanisole were added to a reactor filled with nitrogen and equipped with a mechanical stirrer and a thermometer. After stirring and melting, the mixture was subjected to transesterification reactions at 160°C for 1 hour, 170°C for 1 hour, and 180°C for 2 hours. Then, 0.0561 g (0.05% wt) of tetrabutyl titanate was added, the temperature was raised to 220°C, and the mixture was subjected to vacuum polycondensation for 4 hours to obtain a poly-2,5-furandicarboxylate-based thermoplastic polyester elastomer. The number average molecular weight of the elastomer was 6.9×10 4 .

[0054] Example 4

[0055] 1. 73.66 g (0.4000 mol) of dimethyl 2,5-furandicarboxylate, 39.72 g (0.6400 mol) of ethylene glycol, 0.1134 g (0.10% wt) of zinc acetate, 0.0567 g (0.05% wt) of trimethyl phosphate and 0.1701 g (0.15% wt) of antioxidant 1010 were added to a reactor filled with nitrogen and containing a mechanical stirring device and a thermometer, and the reaction was carried out at a temperature of 180° C. for 1 h, and then at a temperature of 190° C. for 3 h, during which nitrogen was continuously introduced into the reactor. After that, 0.1134 g (0.10% wt) of antimony trioxide was added, and the reaction temperature was gradually increased to 240° C., and the pressure inside the reactor was gradually reduced from one atmosphere to 1 kPa. Under these conditions, the reaction was carried out for 4 h to finally obtain a hydroxyl-terminated prepolymer A. The number average molecular weight was determined by gel permeation chromatography to be 4.5×10 3 .

[0056] 2. 49.60 g (0.4200 mol) of succinic acid, 61.38 g (0.4200 mol) of adipic acid, 84.95 g (0.4200 mol) of sebacic acid, 52.74 g (0.6930 mol) of 1,3-propylene glycol, 62.45 g (0.6930 mol) of 1,4-butanediol, 0.1556 g (0.05% wt) of antioxidant 168 and 0.1556 g (0.05% wt) of antioxidant 1010 were added to a mixture filled with nitrogen and containing a mechanical stirrer. In a reactor equipped with a stirring device and a thermometer, the reaction temperature was gradually increased from 140°C to 190°C, and the reaction was continued for 3 hours under stirring and nitrogen atmosphere. Then, 0.3111g (0.10% wt) of stannous oxalate, 0.4667g (0.15% wt) of antioxidant 168, and 0.4667g (0.15% wt) of antioxidant 1010 were added. The reaction temperature was gradually increased to 220°C, and the pressure in the reactor was gradually reduced from one atmospheric pressure to 1 kPa. The reaction was continued for 4 hours under stirring to finally obtain a hydroxyl-terminated prepolymer B. The number average molecular weight of the prepolymer was 9.7×10 3 The glass transition temperature of the composite was measured by differential scanning calorimetry to be -56.8°C.

[0057] 3. 5.00 g of prepolymer A and 15.00 g of prepolymer B were added to a reactor filled with nitrogen and equipped with a mechanical stirrer. The mixture was melt-mixed by mechanical stirring at 230°C. After the two prepolymers were completely melted, a chain extender, HDI, was added. The ratio of the number of moles of isocyanate in the chain extender to the number of moles of hydroxyl in the two prepolymers was 1.25:1. After 30 minutes of reaction, the pressure in the reactor was gradually reduced from 1 atmosphere to 1 kPa. The reaction was continued for 30 minutes to obtain a poly-2,5-furandicarboxylate-based thermoplastic polyester elastomer. The number average molecular weight was measured by gel permeation chromatography to be 8.4×10 4 .

[0058] Comparative Example 4

[0059] 1. 49.60 g (0.4200 mol) of succinic acid, 61.38 g (0.4200 mol) of adipic acid, 84.95 g (0.4200 mol) of sebacic acid, 52.74 g (0.6930 mol) of 1,3-propylene glycol, 62.45 g (0.6930 mol) of 1,4-butanediol, 0.1556 g (0.05% wt) of antioxidant 168 and 0.1556 g (0.05% wt) of antioxidant 1010 were added to a nitrogen-filled, mechanically In a reactor equipped with a stirring device and a thermometer, the reaction temperature was gradually increased from 140°C to 190°C, and the reaction was continued for 3 hours under stirring and a nitrogen atmosphere. Subsequently, 0.3111 g (0.10% wt) of stannous oxalate, 0.4667 g (0.15% wt) of antioxidant 168, and 0.4667 g (0.15% wt) of antioxidant 1010 were added. The reaction temperature was gradually increased to 220°C, and the pressure in the reactor was gradually reduced from one atmospheric pressure to 1 kPa. The reaction was continued for 4 hours under stirring to finally obtain a hydroxyl-terminated polyester. The number average molecular weight of the polyester was 9.7×10 3 .

[0060] 2. 18.42 g (0.1000 mol) of dimethyl 2,5-furandicarboxylate, 8.07 g (0.1300 mol) of ethylene glycol, 64.26 g of hydroxyl-terminated polyester, and 0.1815 g (0.20% wt) of p-hydroxyanisole were added to a reactor filled with nitrogen and equipped with a mechanical stirrer and a thermometer. After stirring and melting, the mixture was subjected to transesterification reactions at 160°C for 1 hour, 170°C for 1 hour, and 180°C for 2 hours. Then, 0.0454 g (0.05% wt) of tetrabutyl titanate was added, the temperature was raised to 220°C, and the mixture was subjected to vacuum polycondensation for 4 hours to obtain a poly-2,5-furandicarboxylate-based thermoplastic polyester elastomer. The number average molecular weight of the elastomer was 6.9×10 4 .

[0061] Example 5

[0062] 1. 73.66 g (0.4000 mol) of dimethyl 2,5-furandicarboxylate, 39.72 g (0.6400 mol) of ethylene glycol, 0.1134 g (0.10% wt) of zinc acetate, 0.0567 g (0.05% wt) of trimethyl phosphate and 0.1701 g (0.15% wt) of antioxidant 1010 were added to a reactor filled with nitrogen and containing a mechanical stirring device and a thermometer, and the reaction was carried out at a temperature of 180° C. for 1 h, and then at a temperature of 190° C. for 3 h, during which nitrogen was continuously introduced into the reactor. After that, 0.1134 g (0.10% wt) of antimony trioxide was added, and the reaction temperature was gradually increased to 240° C., and the pressure inside the reactor was gradually reduced from one atmosphere to 1 kPa. Under these conditions, the reaction was carried out for 4 h to finally obtain a hydroxyl-terminated prepolymer A. The number average molecular weight was determined by gel permeation chromatography to be 4.5×10 3 .

[0063] 2. 49.60 g (0.4200 mol) of succinic acid, 61.38 g (0.4200 mol) of adipic acid, 84.95 g (0.4200 mol) of sebacic acid, 52.74 g (0.6930 mol) of 1,3-propylene glycol, 62.45 g (0.6930 mol) of 1,4-butanediol, 0.1556 g (0.05% wt) of antioxidant 168 and 0.1556 g (0.05% wt) of antioxidant 1010 were added to a mixture filled with nitrogen and containing a mechanical stirrer. In a reactor equipped with a stirring device and a thermometer, the reaction temperature was gradually increased from 140°C to 190°C, and the reaction was continued for 3 hours under stirring and nitrogen atmosphere. Then, 0.3111g (0.10% wt) of stannous oxalate, 0.4667g (0.15% wt) of antioxidant 168, and 0.4667g (0.15% wt) of antioxidant 1010 were added. The reaction temperature was gradually increased to 220°C, and the pressure in the reactor was gradually reduced from one atmospheric pressure to 1 kPa. The reaction was continued for 4 hours under stirring to finally obtain a hydroxyl-terminated prepolymer B. The number average molecular weight of the prepolymer was 9.7×10 3 The glass transition temperature of the composite was measured by differential scanning calorimetry to be -56.8°C.

[0064] 3. 6.00 g of prepolymer A and 14.00 g of prepolymer B were added to a nitrogen-filled reactor equipped with a mechanical stirrer and melt-mixed at 230°C by mechanical stirring. After the two prepolymers were completely melted, a chain extender, HDI, was added, wherein the ratio of the number of moles of isocyanate in the chain extender to the number of moles of hydroxyl in the two prepolymers was 1.25:1. After 30 minutes of reaction, the pressure in the reactor was gradually reduced from 1 atmosphere to 1 kPa, and the reaction was continued for 30 minutes to obtain a poly-2,5-furandicarboxylate-based thermoplastic polyester elastomer. The number average molecular weight was measured by gel permeation chromatography to be 8.1×10 4 .

[0065] Comparative Example 5

[0066] 1. 49.60 g (0.4200 mol) of succinic acid, 61.38 g (0.4200 mol) of adipic acid, 84.95 g (0.4200 mol) of sebacic acid, 52.74 g (0.6930 mol) of 1,3-propylene glycol, 62.45 g (0.6930 mol) of 1,4-butanediol, 0.1556 g (0.05% wt) of antioxidant 168 and 0.1556 g (0.05% wt) of antioxidant 1010 were added to a nitrogen-filled, mechanically In a reactor equipped with a stirring device and a thermometer, the reaction temperature was gradually increased from 140°C to 190°C, and the reaction was continued for 3 hours under stirring and a nitrogen atmosphere. Subsequently, 0.3111 g (0.10% wt) of stannous oxalate, 0.4667 g (0.15% wt) of antioxidant 168, and 0.4667 g (0.15% wt) of antioxidant 1010 were added. The reaction temperature was gradually increased to 220°C, and the pressure in the reactor was gradually reduced from one atmospheric pressure to 1 kPa. The reaction was continued for 4 hours under stirring to finally obtain a hydroxyl-terminated polyester. The number average molecular weight of the polyester was 9.7×10 3 .

[0067] 2. 18.42 g (0.1000 mol) of dimethyl 2,5-furandicarboxylate, 8.07 g (0.1300 mol) of ethylene glycol, 49.98 g of hydroxyl-terminated polyester, and 0.1529 g (0.20% wt) of p-hydroxyanisole were added to a reactor filled with nitrogen and equipped with a mechanical stirrer and a thermometer. After stirring and melting, the mixture was subjected to transesterification reactions at 160°C for 1 hour, 170°C for 1 hour, and 180°C for 2 hours. Then, 0.0382 g (0.05% wt) of tetrabutyl titanate was added, the temperature was raised to 220°C, and the mixture was subjected to vacuum polycondensation reaction for 4 hours to obtain a poly-2,5-furandicarboxylate-based thermoplastic polyester elastomer. The number average molecular weight of the elastomer was 6.6×10 4 .

[0068] Example 6

[0069] 1. 73.66 g (0.4000 mol) of dimethyl 2,5-furandicarboxylate, 39.72 g (0.6400 mol) of ethylene glycol, 0.1134 g (0.10% wt) of zinc acetate, 0.0567 g (0.05% wt) of trimethyl phosphate and 0.1701 g (0.15% wt) of antioxidant 1010 were added to a reactor filled with nitrogen and containing a mechanical stirring device and a thermometer, and the reaction was carried out at a temperature of 180° C. for 1 h, and then at a temperature of 190° C. for 3 h, during which nitrogen was continuously introduced into the reactor. After that, 0.1134 g (0.10% wt) of antimony trioxide was added, and the reaction temperature was gradually increased to 240° C., and the pressure inside the reactor was gradually reduced from one atmosphere to 1 kPa. Under these conditions, the reaction was carried out for 4 h to finally obtain a hydroxyl-terminated prepolymer A. The number average molecular weight was determined by gel permeation chromatography to be 4.5×10 3 .

[0070] 2. 49.60 g (0.4200 mol) of succinic acid, 61.38 g (0.4200 mol) of adipic acid, 84.95 g (0.4200 mol) of sebacic acid, 52.74 g (0.6930 mol) of 1,3-propylene glycol, 62.45 g (0.6930 mol) of 1,4-butanediol, 0.1556 g (0.05% wt) of antioxidant 168 and 0.1556 g (0.05% wt) of antioxidant 1010 were added to a mixture filled with nitrogen and containing a mechanical stirrer. In a reactor equipped with a stirring device and a thermometer, the reaction temperature was gradually increased from 140°C to 190°C, and the reaction was continued for 3 hours under stirring and nitrogen atmosphere. Then, 0.3111g (0.10% wt) of stannous oxalate, 0.4667g (0.15% wt) of antioxidant 168, and 0.4667g (0.15% wt) of antioxidant 1010 were added. The reaction temperature was gradually increased to 220°C, and the pressure in the reactor was gradually reduced from one atmospheric pressure to 1 kPa. The reaction was continued for 4 hours under stirring to finally obtain a hydroxyl-terminated prepolymer B. The number average molecular weight of the prepolymer was 9.7×10 3 The glass transition temperature of the composite was measured by differential scanning calorimetry to be -56.8°C.

[0071] 3. 7.00 g of prepolymer A and 13.00 g of prepolymer B were added to a reactor filled with nitrogen and equipped with a mechanical stirrer. They were melt mixed by mechanical stirring at a temperature of 230°C. After the two prepolymers were completely melted, a chain extender HDI was added, wherein the ratio of the number of moles of isocyanate in the chain extender to the number of moles of hydroxyl in the two prepolymers was 1.25:1. After 30 minutes of reaction, the pressure in the reactor was gradually reduced from 1 atmosphere to 1 kPa, and the reaction was continued for 30 minutes to obtain a poly-2,5-furandicarboxylate-based thermoplastic polyester elastomer. The number average molecular weight was measured by gel permeation chromatography to be 8.0×10 4 .

[0072] Comparative Example 6

[0073] 1. 49.60 g (0.4200 mol) of succinic acid, 61.38 g (0.4200 mol) of adipic acid, 84.95 g (0.4200 mol) of sebacic acid, 52.74 g (0.6930 mol) of 1,3-propylene glycol, 62.45 g (0.6930 mol) of 1,4-butanediol, 0.1556 g (0.05% wt) of antioxidant 168 and 0.1556 g (0.05% wt) of antioxidant 1010 were added to a nitrogen-filled, mechanically In a reactor equipped with a stirring device and a thermometer, the reaction temperature was gradually increased from 140°C to 190°C, and the reaction was continued for 3 hours under stirring and a nitrogen atmosphere. Subsequently, 0.3111 g (0.10% wt) of stannous oxalate, 0.4667 g (0.15% wt) of antioxidant 168, and 0.4667 g (0.15% wt) of antioxidant 1010 were added. The reaction temperature was gradually increased to 220°C, and the pressure in the reactor was gradually reduced from one atmospheric pressure to 1 kPa. The reaction was continued for 4 hours under stirring to finally obtain a hydroxyl-terminated polyester. The number average molecular weight of the polyester was 9.7×10 3 .

[0074] 2. 18.42 g (0.1000 mol) of dimethyl 2,5-furandicarboxylate, 8.07 g (0.1300 mol) of ethylene glycol, 39.78 g of hydroxyl-terminated polyester, and 0.1325 g (0.20% wt) of p-hydroxyanisole were added to a reactor filled with nitrogen and equipped with a mechanical stirrer and a thermometer. After stirring and melting, the mixture was subjected to transesterification reactions at 160°C for 1 hour, 170°C for 1 hour, and 180°C for 2 hours. Then, 0.0331 g (0.05% wt) of tetrabutyl titanate was added, the temperature was raised to 220°C, and the mixture was subjected to vacuum polycondensation reaction for 4 hours to obtain a poly-2,5-furandicarboxylate-based thermoplastic polyester elastomer. The number average molecular weight of the elastomer was 6.4×10 4 .

[0075] Example 7

[0076] 1. 73.66 g (0.4000 mol) of dimethyl 2,5-furandicarboxylate, 39.72 g (0.6400 mol) of ethylene glycol, 0.1134 g (0.10% wt) of zinc acetate, 0.0567 g (0.05% wt) of trimethyl phosphate and 0.1701 g (0.15% wt) of antioxidant 1010 were added to a reactor filled with nitrogen and containing a mechanical stirring device and a thermometer, and the reaction was carried out at a temperature of 180° C. for 1 h, and then at a temperature of 190° C. for 3 h, during which nitrogen was continuously introduced into the reactor. After that, 0.1134 g (0.10% wt) of antimony trioxide was added, and the reaction temperature was gradually increased to 240° C., and the pressure inside the reactor was gradually reduced from one atmosphere to 1 kPa. Under these conditions, the reaction was carried out for 4 h to finally obtain a hydroxyl-terminated prepolymer A. The number average molecular weight was determined by gel permeation chromatography to be 4.5×10 3 .

[0077] 2. 49.60 g (0.4200 mol) of succinic acid, 61.38 g (0.4200 mol) of adipic acid, 84.95 g (0.4200 mol) of sebacic acid, 52.74 g (0.6930 mol) of 1,3-propylene glycol, 62.45 g (0.6930 mol) of 1,4-butanediol, 0.1556 g (0.05% wt) of antioxidant 168 and 0.1556 g (0.05% wt) of antioxidant 1010 were added to a mixture filled with nitrogen and containing a mechanical stirrer. In a reactor equipped with a stirring device and a thermometer, the reaction temperature was gradually increased from 140°C to 190°C, and the reaction was continued for 3 hours under stirring and nitrogen atmosphere. Then, 0.3111g (0.10% wt) of stannous oxalate, 0.4667g (0.15% wt) of antioxidant 168, and 0.4667g (0.15% wt) of antioxidant 1010 were added. The reaction temperature was gradually increased to 220°C, and the pressure in the reactor was gradually reduced from one atmospheric pressure to 1 kPa. The reaction was continued for 4 hours under stirring to finally obtain a hydroxyl-terminated prepolymer B. The number average molecular weight of the prepolymer was 9.7×10 3 The glass transition temperature of the composite was measured by differential scanning calorimetry to be -56.8°C.

[0078] 3. 8.00 g of prepolymer A and 12.00 g of prepolymer B were added to a reactor filled with nitrogen and equipped with a mechanical stirrer. The mixture was melt-mixed at 230°C by mechanical stirring. After the two prepolymers were completely melted, a chain extender, HDI, was added. The ratio of the number of moles of isocyanate in the chain extender to the number of moles of hydroxyl in the two prepolymers was 1.25:1. After 30 minutes of reaction, the pressure in the reactor was gradually reduced from 1 atmosphere to 1 kPa. The reaction was continued for 30 minutes to obtain a poly-2,5-furandicarboxylate-based thermoplastic polyester elastomer. The number average molecular weight was measured by gel permeation chromatography to be 7.8×10 4 .

[0079] Comparative Example 7

[0080] 1. 49.60 g (0.4200 mol) of succinic acid, 61.38 g (0.4200 mol) of adipic acid, 84.95 g (0.4200 mol) of sebacic acid, 52.74 g (0.6930 mol) of 1,3-propylene glycol, 62.45 g (0.6930 mol) of 1,4-butanediol, 0.1556 g (0.05% wt) of antioxidant 168 and 0.1556 g (0.05% wt) of antioxidant 1010 were added to a nitrogen-filled, mechanically In a reactor equipped with a stirring device and a thermometer, the reaction temperature was gradually increased from 140°C to 190°C, and the reaction was continued for 3 hours under stirring and a nitrogen atmosphere. Subsequently, 0.3111 g (0.10% wt) of stannous oxalate, 0.4667 g (0.15% wt) of antioxidant 168, and 0.4667 g (0.15% wt) of antioxidant 1010 were added. The reaction temperature was gradually increased to 220°C, and the pressure in the reactor was gradually reduced from one atmospheric pressure to 1 kPa. The reaction was continued for 4 hours under stirring to finally obtain a hydroxyl-terminated polyester. The number average molecular weight of the polyester was 9.7×10 3 .

[0081] 2. 18.42 g (0.1000 mol) of dimethyl 2,5-furandicarboxylate, 8.07 g (0.1300 mol) of ethylene glycol, 32.13 g of hydroxyl-terminated polyester, and 0.1172 g (0.20% wt) of p-hydroxyanisole were added to a reactor filled with nitrogen and equipped with a mechanical stirrer and a thermometer. After stirring and melting, the mixture was subjected to transesterification reactions at 160°C for 1 hour, 170°C for 1 hour, and 180°C for 2 hours. Then, 0.0293 g (0.05% wt) of tetrabutyl titanate was added, the temperature was raised to 220°C, and the mixture was subjected to vacuum polycondensation reaction for 4 hours to obtain a poly-2,5-furandicarboxylate-based thermoplastic polyester elastomer. The number average molecular weight of the elastomer was 5.8×10 4 .

[0082] Example 8

[0083] 1. 73.66 g (0.4000 mol) of dimethyl 2,5-furandicarboxylate, 48.70 g (0.64 mol) of 1,3-propylene glycol, 0.1224 g (0.10% wt) of zinc acetate, 0.0612 g (0.05% wt) of trimethyl phosphate and 0.1835 g (0.15% wt) of antioxidant 1010 were added to a reactor filled with nitrogen and containing a mechanical stirring device and a thermometer, and the reaction was carried out at a temperature of 180° C. for 1 h, and then at a temperature of 190° C. for 3 h, during which nitrogen was continuously introduced into the reactor; then 0.1224 g (0.10% wt) of antimony trioxide was added, and the reaction temperature was gradually increased to 240° C., and the pressure inside the reactor was gradually reduced from one atmosphere to 1 kPa. Under these conditions, the reaction was carried out for 4 h to finally obtain a hydroxyl-terminated prepolymer A. The number average molecular weight was determined by gel permeation chromatography to be 4.7×10 3 .

[0084] 2. 49.60 g (0.4200 mol) of succinic acid, 61.38 g (0.4200 mol) of adipic acid, 84.95 g (0.4200 mol) of sebacic acid, 52.74 g (0.6930 mol) of 1,3-propylene glycol, 62.45 g (0.6930 mol) of 1,4-butanediol, 0.1556 g (0.05% wt) of antioxidant 168 and 0.1556 g (0.05% wt) of antioxidant 1010 were added to a mixture filled with nitrogen and containing a mechanical stirrer. In a reactor equipped with a stirring device and a thermometer, the reaction temperature was gradually increased from 140°C to 190°C, and the reaction was continued for 3 hours under stirring and nitrogen atmosphere. Then, 0.3111g (0.10% wt) of stannous oxalate, 0.4667g (0.15% wt) of antioxidant 168, and 0.4667g (0.15% wt) of antioxidant 1010 were added. The reaction temperature was gradually increased to 220°C, and the pressure in the reactor was gradually reduced from one atmospheric pressure to 1 kPa. The reaction was continued for 4 hours under stirring to finally obtain a hydroxyl-terminated prepolymer B. The number average molecular weight of the prepolymer was 9.7×10 3 The glass transition temperature of the composite was measured by differential scanning calorimetry to be -56.8°C.

[0085] 3. Add 3.00 g of prepolymer A and 17.00 g of prepolymer B to a reactor filled with nitrogen and equipped with a mechanical stirrer. Melt and mix them at 230°C with mechanical stirring. When the two prepolymers are completely melted, add chain extender HDI, where the ratio of the number of moles of isocyanate in the chain extender to the number of moles of hydroxyl in the two prepolymers is 1.25:1. After 30 minutes of reaction, gradually reduce the pressure in the reactor from 1 atmosphere to 1 kPa, and continue the reaction for 30 minutes to obtain a poly-2,5-furandicarboxylate-based thermoplastic polyester elastomer. The number average molecular weight of the elastomer is 8.6×10 4 .

[0086] Example 9

[0087] 1. 73.66 g (0.4000 mol) of dimethyl 2,5-furandicarboxylate, 57.68 g (0.6400 mol) of 1,4-butanediol, 0.1313 g (0.10 wt%) of zinc acetate, 0.0657 g (0.05 wt%) of trimethyl phosphate and 0.1970 g (0.15% wt) of antioxidant 1010 were added to a reactor filled with nitrogen and containing a mechanical stirring device and a thermometer, and the reaction was carried out at a temperature of 180° C. for 1 h, and then at a temperature of 190° C. for 3 h, during which nitrogen was continuously introduced into the reactor; then 0.1313 g (0.10 wt%) of antimony trioxide was added, and the reaction temperature was gradually increased to 240° C., and the pressure inside the reactor was gradually reduced from one atmosphere to 1 kPa. Under these conditions, the reaction was carried out for 4 h to finally obtain a hydroxyl-terminated prepolymer A. The number average molecular weight was 5.1×10 3 .

[0088] 2. 49.60 g (0.4200 mol) of succinic acid, 61.38 g (0.4200 mol) of adipic acid, 84.95 g (0.4200 mol) of sebacic acid, 52.74 g (0.6930 mol) of 1,3-propylene glycol, 62.45 g (0.6930 mol) of 1,4-butanediol, 0.1556 g (0.05% wt) of antioxidant 168 and 0.1556 g (0.05% wt) of antioxidant 1010 were added to a mixture filled with nitrogen and containing a mechanical stirrer. In a reactor equipped with a stirring device and a thermometer, the reaction temperature was gradually increased from 140°C to 190°C, and the reaction was continued for 3 hours under stirring and nitrogen atmosphere. Then, 0.3111g (0.10% wt) of stannous oxalate, 0.4667g (0.15% wt) of antioxidant 168, and 0.4667g (0.15% wt) of antioxidant 1010 were added. The reaction temperature was gradually increased to 220°C, and the pressure in the reactor was gradually reduced from one atmospheric pressure to 1 kPa. The reaction was continued for 4 hours under stirring to finally obtain a hydroxyl-terminated prepolymer B. The number average molecular weight of the prepolymer was 9.7×10 3 The glass transition temperature of the composite was measured by differential scanning calorimetry to be -56.8°C.

[0089] 3. Add 3.00 g of prepolymer A and 17.00 g of prepolymer B to a reactor filled with nitrogen and equipped with a mechanical stirrer. Melt and mix them at 230°C with mechanical stirring. When the two prepolymers are completely melted, add chain extender HDI, where the ratio of the number of moles of isocyanate in the chain extender to the number of moles of hydroxyl in the two prepolymers is 1.25:1. After 30 minutes of reaction, gradually reduce the pressure in the reactor from 1 atmosphere to 1 kPa, and continue the reaction for 30 minutes to obtain a poly-2,5-furandicarboxylate-based thermoplastic polyester elastomer. The number average molecular weight of the elastomer is 8.8×10 4 .

[0090] Example 10

[0091] 1. 73.66 g (0.4000 mol) of dimethyl 2,5-furandicarboxylate, 39.72 g (0.6400 mol) of ethylene glycol, 0.1134 g (0.10% wt) of zinc acetate, 0.0567 g (0.05% wt) of trimethyl phosphate and 0.1701 g (0.15% wt) of antioxidant 1010 were added to a reactor filled with nitrogen and containing a mechanical stirring device and a thermometer, and the reaction was carried out at a temperature of 180° C. for 1 h, and then at a temperature of 190° C. for 3 h, during which nitrogen was continuously introduced into the reactor; then 0.1134 g (0.10% wt) of antimony trioxide was added, and the reaction temperature was gradually increased to 240° C., and the pressure inside the reactor was gradually reduced from one atmosphere to 1 kPa. Under these conditions, the reaction was carried out for 4 h to finally obtain a hydroxyl-terminated prepolymer A. The number average molecular weight was determined by gel permeation chromatography to be 4.5×10 3 .

[0092] 2. 48.75 g (0.4200 mol) of fumaric acid, 61.38 g (0.4200 mol) of adipic acid, 84.95 g (0.4200 mol) of sebacic acid, 52.74 g (0.6930 mol) of 1,3-propylene glycol, 62.45 g (0.6930 mol) of 1,4-butanediol, 0.1551 g (0.05% wt) of antioxidant 168 and 0.1551 g (0.05% wt) of antioxidant 1010 were added to a mixture of 1% ethanol and 1% ethanol. In a reactor equipped with a stirring device and a thermometer, the reaction temperature was gradually increased from 140°C to 190°C, and the reaction was continued for 3 hours under stirring and nitrogen atmosphere. Then, 0.3103g (0.10% wt) of stannous oxalate, 0.4654g (0.15% wt) of antioxidant 168, and 0.4654g (0.15% wt) of antioxidant 1010 were added. The reaction temperature was gradually increased to 220°C, and the pressure in the reactor was gradually reduced from one atmospheric pressure to 1 kPa. The reaction was continued for 4 hours under stirring to finally obtain a hydroxyl-terminated prepolymer B. The number average molecular weight of the prepolymer was 9.6×10 3 The glass transition temperature of the composite was measured by differential scanning calorimetry to be -57.2°C.

[0093] 3. Add 3.00 g of prepolymer A and 17.00 g of prepolymer B to a reactor filled with nitrogen and equipped with a mechanical stirrer. Melt and mix them at 230°C with mechanical stirring. When the two prepolymers are completely melted, add chain extender HDI, where the ratio of the number of moles of isocyanate in the chain extender to the number of moles of hydroxyl in the two prepolymers is 1.25:1. After 30 minutes of reaction, gradually reduce the pressure in the reactor from 1 atmosphere to 1 kPa, and continue the reaction for 30 minutes to obtain a poly-2,5-furandicarboxylate-based thermoplastic polyester elastomer. The number average molecular weight of the elastomer is 8.5×10 4 .

[0094] Example 11

[0095] 1. 73.66 g (0.4000 mol) of dimethyl 2,5-furandicarboxylate, 39.72 g (0.6400 mol) of ethylene glycol, 0.1134 g (0.10% wt) of zinc acetate, 0.0567 g (0.05% wt) of trimethyl phosphate and 0.1701 g (0.15% wt) of antioxidant 1010 were added to a reactor filled with nitrogen and containing a mechanical stirring device and a thermometer, and the reaction was carried out at a temperature of 180° C. for 1 h, and then at a temperature of 190° C. for 3 h, during which nitrogen was continuously introduced into the reactor; then 0.1134 g (0.10% wt) of antimony trioxide was added, and the reaction temperature was gradually increased to 240° C., and the pressure inside the reactor was gradually reduced from one atmosphere to 1 kPa. Under these conditions, the reaction was carried out for 4 h to finally obtain a hydroxyl-terminated prepolymer A. The number average molecular weight was determined by gel permeation chromatography to be 4.5×10 3 .

[0096] 2. 49.60 g (0.4200 mol) of succinic acid, 61.38 g (0.4200 mol) of adipic acid, 73.16 g (0.4200 mol) of suberic acid, 84.95 g (0.4200 mol) of sebacic acid, 46.88 g (0.6160 mol) of 1,3-propylene glycol, 55.51 g (0.6160 mol) of 1,4-butanediol, 72.80 g (0.6160 mol) of 1,6-hexanediol, 0.2221 g (0.05% wt) of antioxidant 168 and 0.2221 g (0.05% wt) of wt) of antioxidant 1010 was added to a reactor filled with nitrogen and equipped with a mechanical stirrer and a thermometer. The reaction temperature was gradually increased from 140°C to 190°C and the reaction was continued for 3 hours under stirring and nitrogen atmosphere. Then, 0.4443g (0.10%wt) of stannous oxalate, 0.6664g (0.15%wt) of antioxidant 168 and 0.6664g (0.15%wt) of antioxidant 1010 were added. The reaction temperature was gradually increased to 220°C, and the pressure in the reactor was gradually reduced from one atmospheric pressure to 1 kPa. The reaction was continued for 4 hours under stirring to finally obtain a hydroxyl-terminated prepolymer B. The number average molecular weight thereof was measured by gel permeation chromatography to be 9.7×10 3 The glass transition temperature of the composite was measured by differential scanning calorimetry to be -56.5°C.

[0097] 3. Add 3.00 g of prepolymer A and 17.00 g of prepolymer B to a reactor filled with nitrogen and equipped with a mechanical stirrer. Melt and mix them at 230°C with mechanical stirring. When the two prepolymers are completely melted, add chain extender HDI, where the ratio of the number of moles of isocyanate in the chain extender to the number of moles of hydroxyl in the two prepolymers is 1.25:1. After 30 minutes of reaction, gradually reduce the pressure in the reactor from 1 atmosphere to 1 kPa, and continue the reaction for 30 minutes to obtain a poly-2,5-furandicarboxylate-based thermoplastic polyester elastomer. The number average molecular weight of the elastomer is 8.9×10 4 .

[0098] Example 12

[0099] 1. 73.66 g (0.4000 mol) of dimethyl 2,5-furandicarboxylate, 39.72 g (0.6400 mol) of ethylene glycol, 0.1134 g (0.10% wt) of zinc acetate, 0.0567 g (0.05% wt) of trimethyl phosphate and 0.1701 g (0.15% wt) of antioxidant 1010 were added to a reactor filled with nitrogen and containing a mechanical stirring device and a thermometer, and the reaction was carried out at a temperature of 180° C. for 1 h, and then at a temperature of 190° C. for 3 h, during which nitrogen was continuously introduced into the reactor; then 0.1134 g (0.10% wt) of antimony trioxide was added, and the reaction temperature was gradually increased to 240° C., and the pressure inside the reactor was gradually reduced from one atmosphere to 1 kPa. Under these conditions, the reaction was carried out for 6 h to finally obtain a hydroxyl-terminated prepolymer A. The number average molecular weight was determined by gel permeation chromatography to be 6.7×10 3 .

[0100] 2. 49.60 g (0.4200 mol) of succinic acid, 61.38 g (0.4200 mol) of adipic acid, 84.95 g (0.4200 mol) of sebacic acid, 52.74 g (0.6930 mol) of 1,3-propylene glycol, 62.45 g (0.6930 mol) of 1,4-butanediol, 0.1556 g (0.05% wt) of antioxidant 168 and 0.1556 g (0.05% wt) of antioxidant 1010 were added to a mixture filled with nitrogen and containing a mechanical stirrer. In a reactor equipped with a stirring device and a thermometer, the reaction temperature was gradually increased from 140°C to 190°C, and the reaction was continued for 3 hours under stirring and nitrogen atmosphere. Then, 0.3111g (0.10% wt) of stannous oxalate, 0.4667g (0.15% wt) of antioxidant 168, and 0.4667g (0.15% wt) of antioxidant 1010 were added. The reaction temperature was gradually increased to 220°C, and the pressure in the reactor was gradually reduced from one atmospheric pressure to 1 kPa. The reaction was continued for 4 hours under stirring to finally obtain a hydroxyl-terminated prepolymer B. The number average molecular weight of the prepolymer was 9.7×10 3 The glass transition temperature of the composite was measured by differential scanning calorimetry to be -56.8°C.

[0101] 3. Add 3.00 g of prepolymer A and 17.00 g of prepolymer B to a reactor filled with nitrogen and equipped with a mechanical stirrer. Melt and mix them at 230°C with mechanical stirring. When the two prepolymers are completely melted, add chain extender HDI, where the ratio of the number of moles of isocyanate in the chain extender to the number of moles of hydroxyl in the two prepolymers is 1.25:1. After 30 minutes of reaction, gradually reduce the pressure in the reactor from 1 atmosphere to 1 kPa, and continue the reaction for 30 minutes to obtain a poly-2,5-furandicarboxylate-based thermoplastic polyester elastomer. The number average molecular weight of the elastomer is 9.1×10 4 .

[0102] Example 13

[0103] 1. 73.66 g (0.4000 mol) of dimethyl 2,5-furandicarboxylate, 39.72 g (0.6400 mol) of ethylene glycol, 0.1134 g (0.10% wt) of zinc acetate, 0.0567 g (0.05% wt) of trimethyl phosphate and 0.1701 g (0.15% wt) of antioxidant 1010 were added to a reactor filled with nitrogen and containing a mechanical stirring device and a thermometer, and the reaction was carried out at a temperature of 180° C. for 1 h, and then at a temperature of 190° C. for 3 h, during which nitrogen was continuously introduced into the reactor; then 0.1134 g (0.10% wt) of antimony trioxide was added, and the reaction temperature was gradually increased to 240° C., and the pressure inside the reactor was gradually reduced from one atmosphere to 1 kPa. Under these conditions, the reaction was carried out for 4 h to finally obtain a hydroxyl-terminated prepolymer A. The number average molecular weight was determined by gel permeation chromatography to be 4.5×10 3 .

[0104] 2. 49.60 g (0.4200 mol) of succinic acid, 61.38 g (0.4200 mol) of adipic acid, 84.95 g (0.4200 mol) of sebacic acid, 52.74 g (0.6930 mol) of 1,3-propylene glycol, 62.45 g (0.6930 mol) of 1,4-butanediol, 0.1556 g (0.05% wt) of antioxidant 168 and 0.1556 g (0.05% wt) of antioxidant 1010 were added to a mixture filled with nitrogen and containing a mechanical stirrer. In a reactor equipped with a stirring device and a thermometer, the reaction temperature was gradually increased from 140°C to 190°C, and the reaction was continued for 3 hours under stirring and nitrogen atmosphere; then 0.3111g (0.10% wt) of stannous oxalate, 0.4667g (0.15% wt) of antioxidant 168, and 0.4667g (0.15% wt) of antioxidant 1010 were added, the reaction temperature was gradually increased to 220°C, and the pressure in the reactor was gradually reduced from one atmospheric pressure to 1 kPa. The reaction was continued for 6 hours under stirring to finally obtain a hydroxyl-terminated prepolymer B. The number average molecular weight of the prepolymer was 1.4×10 4 The glass transition temperature of the composite was measured by differential scanning calorimetry to be -54.7°C.

[0105] 3. Add 3.00 g of prepolymer A and 17.00 g of prepolymer B to a reactor filled with nitrogen and equipped with a mechanical stirrer, and melt mix them at 230°C with mechanical stirring. When the two prepolymers are completely melted, add chain extender HDI, wherein the ratio of the number of moles of isocyanate in the chain extender to the number of moles of hydroxyl in the two prepolymers is 1.25:1. After 30 minutes of reaction, the pressure in the reactor is gradually reduced from 1 atmosphere to 1 kPa, and the reaction is continued for 30 minutes to obtain a poly-2,5-furandicarboxylate-based thermoplastic polyester elastomer. The number average molecular weight measured by gel permeation chromatography is 1.0×10 5 .

[0106] Example 14

[0107] 1. 73.66 g (0.4000 mol) of dimethyl 2,5-furandicarboxylate, 39.72 g (0.6400 mol) of ethylene glycol, 0.1134 g (0.10% wt) of zinc acetate, 0.0567 g (0.05% wt) of trimethyl phosphate and 0.1701 g (0.15% wt) of antioxidant 1010 were added to a reactor filled with nitrogen and containing a mechanical stirring device and a thermometer, and the reaction was carried out at a temperature of 180° C. for 1 h, and then at a temperature of 190° C. for 3 h, during which nitrogen was continuously introduced into the reactor; then 0.1134 g (0.10% wt) of antimony trioxide was added, and the reaction temperature was gradually increased to 240° C., and the pressure inside the reactor was gradually reduced from one atmosphere to 1 kPa. Under these conditions, the reaction was carried out for 6 h to finally obtain a hydroxyl-terminated prepolymer A. The number average molecular weight was determined by gel permeation chromatography to be 6.7×10 3 .

[0108] 2. 49.60 g (0.4200 mol) of succinic acid, 61.38 g (0.4200 mol) of adipic acid, 84.95 g (0.4200 mol) of sebacic acid, 52.74 g (0.6930 mol) of 1,3-propylene glycol, 62.45 g (0.6930 mol) of 1,4-butanediol, 0.1556 g (0.05% wt) of antioxidant 168 and 0.1556 g (0.05% wt) of antioxidant 1010 were added to a mixture filled with nitrogen and containing a mechanical stirrer. In a reactor equipped with a stirring device and a thermometer, the reaction temperature was gradually increased from 140°C to 190°C, and the reaction was continued for 3 hours under stirring and nitrogen atmosphere; then 0.3111g (0.10% wt) of stannous oxalate, 0.4667g (0.15% wt) of antioxidant 168, and 0.4667g (0.15% wt) of antioxidant 1010 were added, the reaction temperature was gradually increased to 220°C, and the pressure in the reactor was gradually reduced from one atmospheric pressure to 1 kPa. The reaction was continued for 6 hours under stirring to finally obtain a hydroxyl-terminated prepolymer B. The number average molecular weight of the prepolymer was 1.4×10 4 The glass transition temperature of the composite was measured by differential scanning calorimetry to be -54.7°C.

[0109] 3. Add 3.00 g of prepolymer A and 17.00 g of prepolymer B to a reactor filled with nitrogen and equipped with a mechanical stirrer. Melt and mix them at 230°C with mechanical stirring. When the two prepolymers are completely melted, add chain extender HDI, where the ratio of the number of moles of isocyanate in the chain extender to the number of moles of hydroxyl in the two prepolymers is 1.25:1. After 30 minutes of reaction, gradually reduce the pressure in the reactor from 1 atmosphere to 1 kPa, and continue the reaction for 30 minutes to obtain a poly-2,5-furandicarboxylate-based thermoplastic polyester elastomer. The number average molecular weight of the elastomer is 1.6×10 5 .

[0110] Example 15

[0111] 1. 73.66 g (0.4000 mol) of dimethyl 2,5-furandicarboxylate, 39.72 g (0.6400 mol) of ethylene glycol, 0.1134 g (0.10% wt) of zinc acetate, 0.0567 g (0.05% wt) of trimethyl phosphate and 0.1701 g (0.15% wt) of antioxidant 1010 were added to a reactor filled with nitrogen and containing a mechanical stirring device and a thermometer, and the reaction was carried out at a temperature of 180° C. for 1 h, and then at a temperature of 190° C. for 3 h, during which nitrogen was continuously introduced into the reactor; then 0.1134 g (0.10% wt) of antimony trioxide was added, and the reaction temperature was gradually increased to 240° C., and the pressure inside the reactor was gradually reduced from one atmosphere to 1 kPa. Under these conditions, the reaction was carried out for 4 h to finally obtain a hydroxyl-terminated prepolymer A. The number average molecular weight was determined by gel permeation chromatography to be 4.5×10 3 .

[0112] 2. 49.60 g (0.4200 mol) of succinic acid, 61.38 g (0.4200 mol) of adipic acid, 84.95 g (0.4200 mol) of sebacic acid, 52.74 g (0.6930 mol) of 1,3-propylene glycol, 62.45 g (0.6930 mol) of 1,4-butanediol, 0.1556 g (0.05% wt) of antioxidant 168 and 0.1556 g (0.05% wt) of antioxidant 1010 were added to a mixture filled with nitrogen and containing a mechanical stirrer. In a reactor equipped with a stirring device and a thermometer, the reaction temperature was gradually increased from 140°C to 190°C, and the reaction was continued for 3 hours under stirring and nitrogen atmosphere. Then, 0.3111g (0.10% wt) of stannous oxalate, 0.4667g (0.15% wt) of antioxidant 168, and 0.4667g (0.15% wt) of antioxidant 1010 were added. The reaction temperature was gradually increased to 220°C, and the pressure in the reactor was gradually reduced from one atmospheric pressure to 1 kPa. The reaction was continued for 4 hours under stirring to finally obtain a hydroxyl-terminated prepolymer B. The number average molecular weight of the prepolymer was 9.7×10 3 The glass transition temperature of the composite was measured by differential scanning calorimetry to be -56.8°C.

[0113] 3. Add 3.00 g of prepolymer A and 17.00 g of prepolymer B to a reactor filled with nitrogen and equipped with a mechanical stirrer, and melt mix them at 230°C by mechanical stirring. When the two prepolymers are completely melted, add a chain extender, diphenylmethane diisocyanate (MDI), wherein the ratio of the number of moles of isocyanate in the chain extender to the number of moles of hydroxyl in the two prepolymers is 1.25:1. After 30 minutes of reaction, the pressure in the reactor is gradually reduced from 1 atmosphere to 1 kPa, and the reaction is continued for 30 minutes to obtain a poly-2,5-furandicarboxylate-based thermoplastic polyester elastomer. The number average molecular weight of the elastomer is 8.6×10 4 .

[0114] Example 16

[0115] 1. 62.44 g (0.4000 mol) of 2,5-furandicarboxylic acid, 22.3445 g (0.3600 mol) of ethylene glycol, 0.1468 g (8 × 10 -4 mol) of zinc acetate, 0.0560 g (4 × 10 -4 mol) of trimethyl phosphate and 0.2120 g (0.25% wt) of antioxidant 1010 were added to a reactor filled with nitrogen and equipped with a mechanical stirrer and a thermometer, and reacted at 180°C for 1 h, and then at 190°C for 3 h, during which nitrogen was continuously introduced into the reactor; then 0.1749 g (6×10 -4mol) of antimony trioxide, and the reaction temperature was gradually increased to 240°C, and the pressure inside the reactor was gradually reduced from one atmosphere to 1 kPa. Under this condition, the reaction was carried out for 4 hours, and finally a carboxyl-terminated prepolymer A was obtained. The number average molecular weight of the prepolymer was 4.7×10 3 .

[0116] 2. 49.60 g (0.4200 mol) of succinic acid, 61.38 g (0.4200 mol) of adipic acid, 84.95 g (0.4200 mol) of sebacic acid, 43.15 g (0.5670 mol) of 1,3-propylene glycol, 51.10 g (0.5670 mol) of 1,4-butanediol, 0.1451 g (0.05% wt) of antioxidant 168 and 0.1451 g (0.05% wt) of antioxidant 1010 were added to a mixture filled with nitrogen and containing a mechanical stirrer. In a reactor equipped with a stirring device and a thermometer, the reaction temperature was gradually increased from 140°C to 190°C, and the reaction was continued for 3 hours under stirring and nitrogen atmosphere. Then, 0.2902g (0.10% wt) of stannous oxalate, 0.4353g (0.15% wt) of antioxidant 168, and 0.4353g (0.15% wt) of antioxidant 1010 were added. The reaction temperature was gradually increased to 220°C, and the pressure in the reactor was gradually reduced from one atmospheric pressure to 1 kPa. The reaction was continued for 4 hours under stirring to finally obtain a carboxyl-terminated prepolymer B. The number average molecular weight of the prepolymer was 9.4×10 3 The glass transition temperature of the composite was measured by differential scanning calorimetry to be -58.1°C.

[0117] 3. Add 3.00 g of prepolymer A and 17.00 g of prepolymer B to a reactor filled with nitrogen and equipped with a mechanical stirrer, and melt mix them at 230°C by mechanical stirring. When the two prepolymers are completely melted, add the chain extender bis((3,4-epoxycyclohexyl)methyl) adipate, wherein the ratio of the molar number of epoxy groups in the chain extender to the molar number of carboxyl groups in the two prepolymers is 1.25:1. After 30 minutes of reaction, the pressure in the reactor is gradually reduced from 1 atmosphere to 1 kPa, and the reaction is continued for 30 minutes to obtain a poly-2,5-furandicarboxylate-based thermoplastic polyester elastomer. The number average molecular weight measured by gel permeation chromatography is 8.3×10 4 .

[0118] Comparative Example 8

[0119] 100.00 g (0.6400 mol) of 2,5-furandicarboxylic acid, 115.00 g (1.2800 mol) of 1,4-butanediol, 50.00 g (0.4400 mol) of ε-caprolactone, 0.3000 g (0.11% wt) of tetrabutyl titanate and 0.1000 g (0.04% wt) of antimony oxide were added to a reaction vessel filled with nitrogen and equipped with a mechanical stirrer and a thermometer. The reaction was carried out in a reactor at 190°C under normal pressure for 6 hours to obtain a thermoplastic polyester prepolymer based on 2,5-furandicarboxylic acid. 0.2000g (0.08% wt) of triphenyl phosphite and 0.3000g (0.11% wt) of germanium oxide were then added to the prepolymer. The mixture was evacuated to 100 Pa and heated to 250°C for 3 hours to obtain a poly-2,5-furandicarboxylic acid ester-based thermoplastic polyester elastomer. The number average molecular weight of the elastomer was 6.2×10- 4 .

[0120] Comparative Example 9

[0121] 1. 45.65 g (0.6000 mol) of 1,2-propylene glycol, 54.07 g (0.6000 mol) of 1,4-butanediol, 82.66 g (0.7000 mol) of 1,4-butanediol, 60.68 g (0.3000 mol) of 1,10-decanedioic acid and 0.4861 g (0.20% wt) of p-hydroxyanisole were added to a reactor filled with nitrogen and containing a mechanical stirring device and a thermometer, and the temperature was raised to 180° C. and reacted at this temperature for 2 h. Then, 0.1215 g (0.05% wt) of tetrabutyl titanate was added and the reaction was carried out under reduced pressure (300 Pa) for 1.5 h. Then, 10.81 g (0.1200 mol) of 1,4-butanediol was added for end-capping to obtain a hydroxyl-terminated polyester. The number average molecular weight was measured by gel permeation chromatography and was 9.5×10 3 .

[0122] 2. 18.42 g (0.1000 mol) of dimethyl 2,5-furandicarboxylate, 11.72 g (0.1300 mol) of 1,4-butanediol, 120.56 g of hydroxyl-terminated polyester, and 0.3014 g (0.20% wt) of p-hydroxyanisole were added to a reactor filled with nitrogen and equipped with a mechanical stirrer and a thermometer. After stirring and melting, the mixture was subjected to transesterification reactions at 160°C for 1 hour, 170°C for 1 hour, and 180°C for 2 hours. 0.0754 g (0.05% wt) of tetrabutyl titanate was then added, the temperature was raised to 220°C, and the mixture was subjected to vacuum polycondensation for 4 hours to obtain a poly-2,5-furandicarboxylate-based thermoplastic polyester elastomer. The number average molecular weight of the elastomer was 5.9 × 10 4 .

[0123] Performance test: Gel permeation chromatography (GPC) was used to characterize the molecular weight

[0124] The mechanical properties are tested according to GB / T 528-2009 standard.

[0125] Biodegradability was tested as follows: the sample was degraded in a lipase solution at 37°C for 15 days, and the sample mass loss (degradation rate, %) was calculated. The lipase solution was prepared by dissolving a predetermined amount of lipase (200,000 U / g) in 250 ml of a mixed phosphate solution (0.025 M) at a pH of 6.86 to obtain a lipase solution with a concentration of 5 mg / ml.

[0126] The specific test results are shown in Table 1 below.

[0127] Table 1. Properties of poly(2,5-furandicarboxylate)-based thermoplastic polyester elastomers

[0128]

[0129]

[0130] Examples 1 to 7 demonstrate that by adjusting the ratio of soft and hard segments, poly(2,5-furandicarboxylate)-based thermoplastic polyester elastomers with varying tensile strength, elongation at break, hardness, and degradation properties can be obtained. Examples 1, 8, and 9 demonstrate that by varying the type of monomers in prepolymer A, poly(2,5-furandicarboxylate)-ethylene glycol prepolymers, poly(2,5-furandicarboxylate)-propylene glycol prepolymers, and poly(2,5-furandicarboxylate)-butylene glycol prepolymers can be obtained, thereby synthesizing different types of poly(2,5-furandicarboxylate)-based thermoplastic polyester elastomers. Examples 10 and 11 demonstrate that by varying the type of monomers in prepolymer B, different molecular structures can be obtained, thereby synthesizing different types of poly(2,5-furandicarboxylate)-based thermoplastic polyester elastomers. Examples 1, 12, 13, and 14 demonstrate that varying the reaction time of the soft and hard segments can yield soft and hard segments of varying molecular weights, and thus poly(2,5-furandicarboxylate)-based thermoplastic polyester elastomers of varying molecular weights, thereby affecting the tensile strength, elongation at break, hardness, and degradation properties of the poly(2,5-furandicarboxylate)-based thermoplastic polyester elastomers. Examples 1, 15, and 16 demonstrate that varying the component ratios can design hydroxyl- or carboxyl-terminated hard and soft segment prepolymers, and that the corresponding poly(2,5-furandicarboxylate)-based thermoplastic polyester elastomers can be obtained by using hydroxyl or carboxyl chain extenders. Through Examples 1 to 16 and Comparative Examples 1 to 9, it can be concluded that the poly-2,5-furandicarboxylic acid alcohol ester-based thermoplastic polyester elastomer prepared by the present invention has excellent mechanical properties, which can be controlled. Its tensile strength is 12.7 to 29.5 MPa, its elongation at break is 984 to 1971%, its hardness is 65.2 to 78.5 HA, and its 15-day degradation rate is 52.6 to 85.3%. In addition, the poly-2,5-furandicarboxylic acid alcohol ester-based thermoplastic polyester elastomer also has excellent rebound resilience, with a 100% tensile recovery rate of 89.3 to 98.2%. By comparing the performance test results of each embodiment with the comparative example, it can be seen that the poly-2,5-furandicarboxylic acid alcohol ester-based thermoplastic polyester elastomer prepared by the present invention can control its mechanical properties and biodegradability by designing the molecular structure, adjusting the molecular weight and the ratio of soft and hard segments, thereby meeting the requirements of use.

[0131] The above-described embodiments merely illustrate several implementations of the present invention, and while their descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that a person skilled in the art would be able to make numerous variations and improvements without departing from the spirit of the present invention, all of which fall within the scope of protection of the present invention. Therefore, the scope of protection of the present invention shall be determined by the appended claims.

Claims

1. A poly-2,5-furandicarboxylate-based thermoplastic polyester elastomer, characterized in that: The thermoplastic polyester elastomer is an AbB type poly-2,5-furandicarboxylic acid alcohol ester-polyester block copolymer synthesized by prepolymer A and prepolymer B through chain extender block reaction; The prepolymer A is a dihydroxy or carboxyl terminated 2,5-furandicarboxylic acid polyester prepolymer prepared by polymerization of a diol and 2,5-furandicarboxylic acid or 2,5-furandicarboxylic acid dimethyl ester; The prepolymer B is a highly flexible aliphatic polyester prepolymer terminated with dihydroxyl or carboxyl groups and prepared by melt polycondensation with various aliphatic diols and dibasic acids, acid anhydrides and / or acid chlorides as monomers; The mass ratio of the prepolymer A to the prepolymer B is 1:1-1:19; The ratio of the molar number of the functional groups in the chain extender to the molar number of the hydroxyl or carboxyl groups in the prepolymer is 1:1-1.3:1; The number average molecular weight of the prepolymer A is 1000-20000; The diol is one of ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 2-methyl-1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,10-decanediol, diethylene glycol, dipropylene glycol, triethylene glycol, tripropylene glycol, PEG-200, PEG-400, PEG-600, PPG-200, PPG-400, PPG-600, or a mixture thereof in any proportion; The number average molecular weight of the highly flexible aliphatic polyester prepolymer B is in the range of 1000-20000; the glass transition temperature of the aliphatic polyester prepolymer B is lower than -40°C; the molecular structure of the aliphatic polyester prepolymer B is composed of more than 4 aliphatic polyester repeating structural units; The dibasic acid, acid anhydride and / or acid chloride is any one of malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, sebacic acid, dodecanedioic acid, tridecanedioic acid, pentadecanedicarboxylic acid, itaconic acid, fumaric acid, succinic anhydride, glutaric anhydride, adipic anhydride, itaconic anhydride, maleic anhydride, succinic dichloride, glutaric dichloride, adipic dichloride, itaconic acid chloride, or a mixture thereof in any proportion; The chain extender is hexamethylene diisocyanate, diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate, isophorone diisocyanate, lysine diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, naphthalene diisocyanate, bis((3,4-epoxycyclohexyl)methyl) adipate, 1,6-hexanedioic acid diglycidyl ether, resorcinol diglycidyl ether, resorcinol formaldehyde tetraglycidyl ether, tetrahydrophenylene dimethyl ether epoxy resin, 1,2-epoxycyclohexane-4,5-dicarboxylic acid epoxy resin, phthalate epoxy resin, isophthalate epoxy resin, terephthalate epoxy resin, endomethylene tetrahydrophthalate epoxy resin, p-hydroxybenzoic acid epoxy resin, bis(2,3-epoxycyclopentyl) ether, ethylene glycol diglycidyl ether, 2,2′-bis(2-oxazoline), 2,2′-(1,3-phenylene)-bisoxazoline, or a mixture thereof in any proportion.

2. A method for preparing the poly-2,5-furandicarboxylate-based thermoplastic polyester elastomer according to claim 1, characterized in that : The preparation method comprises the following steps: (1) Preparation of prepolymer A The diol and 2,5-furandicarboxylic acid or 2,5-furandicarboxylic acid dimethyl ester are mixed at a molar ratio of 0.8-3:1, and a catalyst accounting for 0.01-0.5% of the weight of the monomer and a certain amount of antioxidant and stabilizer are added, and an esterification or transesterification reaction is carried out at a temperature range of 150-200° C. under nitrogen protection for 1-10 hours, and then a certain amount of antioxidant and catalyst are added, and the temperature is raised to 200-270° C. within a pressure range below 2 kPa, and the reaction is continued for 1-8 hours to obtain a dihydroxy or carboxyl terminated prepolymer A; (2) Preparation of prepolymer B A plurality of aliphatic diols and dibasic acids, acid anhydrides and / or acid chlorides are mixed at an alcohol-acid ratio of 1:1.05-1.5 or 1.05-1.5:1, a catalyst accounting for 0.01-0.5% of the monomer mass and a certain amount of antioxidant and stabilizer are added, and the mixture is stirred and heated to 130-180°C in stages under an inert atmosphere for esterification reaction for 1-6 hours, and then an antioxidant is added, and the mixture is stirred and heated to 200-240°C in a pressure range below 2 kPa, and the reaction is continued for 2-8 hours to obtain a dihydroxy or carboxyl terminated highly flexible aliphatic polyester soft segment prepolymer B; (3) Preparation of poly (2,5-furandicarboxylic acid) ester-based thermoplastic polyester elastomer The prepolymer A prepared in step (1) and the prepolymer B prepared in step (2) are mixed, heated to 140-250° C., melt-mixed for 20-60 min under nitrogen protection, and then a chain extender is added for block copolymerization, reacted for 10-60 min, and then continued to react for 0.5-2 h in a pressure range of a vacuum degree of less than 2 kPa, thereby obtaining the poly-2,5-furandicarboxylic acid alcohol ester-based thermoplastic polyester elastomer.

3. The preparation method according to claim 2, characterized in that: The catalyst is selected from trifluoromethanesulfonic acid, methyl trifluoromethanesulfonate, titanium dioxide, titanium glycolate, titanium acetylacetonate, n-butyl titanate, isopropyl titanate, antimony glycolate, antimony trioxide, stannous octoate, stannous oxalate, dibutyltin oxide, dibutyltin dilaurate, butylstannic acid, lithium acetate, potassium acetate, calcium acetate, barium acetate, cobalt acetate, antimony acetate, lead acetate, manganese acetate, triisopropoxyaluminum, zinc acetate, zinc oxide, stannous chloride, concentrated sulfuric acid, p-toluenesulfonic acid, magnesium acetate, zinc chloride, lithium chloride, germanium chloride, tin tetrachloride, potassium carbonate, triethylenediamine, triethylamine, zinc lactate or a mixture thereof in any proportion; The antioxidant is selected from the group consisting of antioxidant 168, antioxidant 240, antioxidant 245, antioxidant 264, antioxidant 300, antioxidant 330, antioxidant 445, antioxidant 1010, antioxidant 1024, antioxidant 1035, antioxidant 1520, antioxidant 1076, antioxidant 1098, antioxidant 1330, antioxidant 1790, antioxidant 2246, and antioxidant 3114, or a mixture thereof in any proportion; The stabilizer is selected from one or more mixtures of phosphoric acid, phosphorous acid, hypophosphorous acid, pyrophosphoric acid, ammonium phosphate, dimethyl phosphate, trimethyl phosphate, diphenyl phosphate, triphenyl phosphate, diphenyl phosphite, triphenyl phosphite, triethyl phosphate, ammonium phosphite, diammonium phosphate, p-hydroxyanisole, hydroquinone, o-methylhydroquinone, and p-benzoquinone.

Citation Information

Patent Citations

  • Thermoplastic polyester elastomer based on biomass-based 2,5-furandicarboxylic acid, and preparation method thereof

    CN107312167A

  • Method for preparing polyester-polyester blocked copolyester

    CN102516517A

  • Furan ring-based full-bio-based thermoplastic polyester elastomer and preparation method thereof

    CN111116880A